Uterine perforation with bowel prolapsing through vagina following an unsafe abortion - Verma, Kamala; Baniya, Girish Chandra (International Journal of Research in Medical Sciences, 2017)
An unwanted pregnancy may lead to induced abortion that means willful termination of pregnancy before the period of viability. Most of the times when termination of pregnancy is done by skilled person in fully aseptic environment, complications are low. But severe complication including uterine perforation, bowel injury, sepsis and sometimes death is common when the procedure is carried out by unskilled personnel in unhealthy condition. This case representing the neglected scenario of our maternal health facilities in rural areas where many untrained care providers are still performing illegal and unsafe abortion without knowledge of its grave consequences.